Introduction - governance and public administration in the 21st century: a research and training prospectus - Olowu, Dele (2002)
This article reviews the different approaches to the study of governance and how the concept and practice of governance is connected with public administration and public management. It examines the controversy surrounding the claim that a paradigm shift has occurred in the study of state-society-economy relationships. This has replaced public administration with public management. The paper suggests that the rediscovery of governance in public administration discourse has enriched the discipline. It then reviews each of the six articles in this special symposium of the IRAS. Issues raised in these articles constitute the agenda for training centres in public administration, policy and management. - Reproduced.
Keywords: Public administration